2013
DOI: 10.1038/bmt.2013.176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of storage temperature on hematopoietic stability and microbial safety of BM aspirates

Abstract: Bone Marrow (BM) remains a common source for hematopoietic SCT. Due to the transcutaneous approach, contamination with skin bacteria is common. The delay between harvest and transfusion can be considerable, potentially allowing for bacterial proliferation. The optimal transportation temperature, specifically with respect to bacterial growth and consequences thereof for hematopoietic quality, remain undefined. For 72 h, 66 individual BM samples, non-spiked/spiked with different bacteria, stored at 20-24 1C room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…As to the temperature regulation, low temperature weakened temperature-dependent chemical bonds in cytoskeletal support, thus leading the cell more vulnerable to mechanical damage [6]. It also indicated that the majority of fresh blood products and sterile BM samples benefitted from transportation at room temperature [7,8]. Similarly, low temperature is not favorable for shipment of retinal tissues in our study.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…As to the temperature regulation, low temperature weakened temperature-dependent chemical bonds in cytoskeletal support, thus leading the cell more vulnerable to mechanical damage [6]. It also indicated that the majority of fresh blood products and sterile BM samples benefitted from transportation at room temperature [7,8]. Similarly, low temperature is not favorable for shipment of retinal tissues in our study.…”
Section: Discussionmentioning
confidence: 65%
“…Important considerations related to transportation include density of tissues, shipment duration, temperature management, and transportation medium [6]. Since the former three considerations have been investigated previously on other organs or stem cells [5,[7][8][9][10], we focused on seeking appropriate anti-apoptotic medium for the first time on transporting hiPSC-differentiated retinal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…As is apparent from Figure 1, Prodigy only minimally reduces process time over CliniMACS Plus, but the hands-on operator time is reduced by almost 2 h. Because the Prodigy process could run unsupervised or supervised remotely overnight, a possible advantage would be avoidance of unfavorable working hours while recovering cells of maximal freshness and, hence, functional quality, given that experience shows approximately linear cell loss over time, starting from the moment that the cells are collected from the donor [21]. The process of CD34 selection is maximally simplified by Prodigy.…”
Section: Discussionmentioning
confidence: 99%
“…However, pathogenic bacteria such as E. coli and S. aureus are capable of rapid expansion within HSC products stored at room temperature. 9 Certain organisms, such as Candida spp and S. aureus, are particularly capable of forming biofilms on foreign material. Contamination with highly virulent organisms, while rare, may expose HCT recipients to much greater risk than contamination with less pathogenic organisms.…”
Section: Staphylococcus Aureus Bloodstream Infection Due To Contaminamentioning
confidence: 99%